Degradation analysis of installed solar photovoltaic (PV) modules under outdoor conditions in Ghana - Aboagye, Bernard; Gyamf, Samuel; Antwi Ofosu, Eric (Energy Reports, 2021)
Photovoltaic (PV) module degradation rate depends on technology, manufacturer and environmental conditions. This makes it challenging to transfer the results of degradation analysis from one country to another. Thus, the increase in deployment of PV systems in Ghana makes degradation analysis a necessity. This study quantified the degradation rates and predicted the lifetime of 16 PV systems of different module technologies and age groups installed in different locations under outdoor conditions in Ghana to provide a better understanding of the long-term behavior of installed PV systems in Ghana. It presented the frequency distribution of output power degradation of different PV module technologies, estimated their power degradation rates, and predicted and compared the lifetime of these technologies. The country was grouped into three strata and 104 PV modules of different technologies which were older than 5 years were selected from 16 PV systems in these strata, depending on availability and accessibility. The electrical parameters of the PV modules were measured by current–voltage (IV) tracing. The results revealed that crystalline silicon modules degraded less than amorphous silicon. The median and mean power degradation rates of, monocrystalline silicon were 1.23%/year and 1.37%/year respectively, polycrystalline silicon were 1.35%/year and 1.44%/year respectively and, amorphous silicon were 1.65%/year and 1.67%/year respectively. Overall, the median and mean predicted lifetime of the PV systems (crystalline and amorphous silicon) were 14 year and 16 years respectively but the median lifetime of both monocrystalline and polycrystalline modules was 16 years while that of amorphous was 13 years. It was predicted that 50% of PV modules studied would fail before 15 years, indicating that most of the PV modules in Ghana are unlikely to operate for the 25 years warranty, signifying less power output and shorter lifetime of the modules which could discourage the widespread implementation of PV systems in Ghana
Keywords: Degradation rate; Lifetime of PV modules; Installed PV systems; Outdoor conditions; Ghana; Sinisa Djordjevic; ACE: Energy and Environmental Sustainability; University of Energy & Natural Resources; Power